PLUME ACTIVITY, MAGMATISM, AND THE GEODYNAMIC EVOLUTION OF THE CENTRAL MEDITERRANEAN - Bell K.; Castorina F.; Rosatelli G.; Stoppa F. (My University, 2006)
On the basis of isotopic and geochemical data we propose that most of the volcanic activity in Italy is plume rather than subduction related. We suggest that a large plume underlies the Tyrrhenian Sea, extending westwards under Sardinia and Corsica, northwards towards the Western Alps and eastwards under the Italian mainland. The plume is isotopically defined in terms of three end-members, different from any of those found in subduction-related environments. Two of the end-members are similar to the FOZO and EM1 mantle components defined on the basis of data from OIBs, while a third, here called ITEM (ITalian Enriched Mantle), is characterized by a high 87Sr/86Sr ratio (>0.7200) and quite different from any component found in oceanic environments. The two trends that emerge in isotope ratio diagrams indicate mixing between a common end-member (FOZO) and the two others. Implied by the presence of a common end-member is the involvement of a common source and a single large-scale geodynamic system. Partial melting of an isotopically heterogeneous plume head containing both source and entrained material is one way to explain many of the features that characterize Italian magmatism. Widespread extensional tectonics, lithospheric thinning, and deep-seated CO2 emissions add further support to mantle plume activity in Italy.